Initial responses of Chinook salmon (Oncorhynchus tshawytscha) and steelhead (Oncorhynchus mykiss) to removal of two dams on the Elwha River, Washington State, U.S.A. - Pess, George R.; McHenry, Michael L.; Denton, Keith; Anderson, Joseph H.; Liermann, Martin C.; Peters, Roger J.; McMillan, John R.; Brenkman, Samuel J.; Bennett, Todd R.; Duda, Jeffrey J.; Hanson, Karrie M. (Frontiers in Ecology and Evolution, 2024)
Large dam removal is being used to restore river systems, but questions remain regarding their outcomes. We examine how the removal of two large dams in the Elwha River, coupled with hatchery production and fishing closures, affected population attributes of Chinook salmon (Oncorhynchus tshawytscha) and steelhead (O. mykiss). Initial responses by returning adult Chinook salmon and steelhead was an increase in the number and spatial extent of natural and hatchery origin fish. Although few naturally produced juvenile Chinook salmon and steelhead outmigrants were observed prior to and during dam removal, abundances increased three years after adult fish passage was restored, suggesting that impacts due to downstream sedimentation after dam removal were reduced. The Chinook salmon population demographics remain dominated by hatchery production, while increases in winter steelhead abundance included both hatchery and natural-origin spawners. The spatial expansion of winter steelhead upstream of former dam sites was predominantly by natural-origin spawners. We also observed a natural “reawakening” of summer steelhead that were in part derived from an up-river resident population that returned to the Upper Elwha. Our results showed that a combination of habitat, hatchery, and harvest actions can result in positive responses for salmonid populations.